"It Was Like I Lost Everything": The Harmful Impacts of Homeless-Targeted Policies. Issue 4 (4th July 2018) - Darrah-Okike, Jennifer; Soakai, Sarah; Nakaoka, Susan; Dunson-Strane, Tai; Umemoto, Karen
Abstract: In response to housing crises across the country, many localities are implementing homeless-targeted policies that attempt to regulate public space by prohibiting sitting, lying, sleeping, and storing property in public places such as parks and sidewalks. We term these sociospatial control policies. Our research investigates the direct impacts of such policies in the city of Honolulu, which had become notorious for legal measures targeting homeless residents. We interviewed members of 70 households living in temporary shelters in public spaces, all of whom had experienced enforcement of city ordinances, such as receiving citations or being forcibly moved by city agents. Our data revealed three interconnected ways that enforcements of sit–lie and nuisance policies harmed homeless households. (a) Our respondents described feeling dehumanized and treated unfairly by city agents. We therefore argue that enforcement catalyzed both civic and social exclusion. (b) Second, the city's confiscation of property spurred material hardship and posed obstacles to work, education, and access to services. And, finally, (c) respondents' narratives revealed that enforcements provoked lasting worry, fear, anxiety, and despair.